Dynamic Trading and Asset Prices: Keynes vs. Hayek - Cespa, G.; Vives, X. (Review of Economic Studies, 2012)
We investigate the dynamics of prices, information, and expectations in a competitive, noisy, dynamic asset pricing equilibrium model with long-term investors. We argue that the fact that prices can score worse or better than consensus opinion in predicting the fundamentals is a product of endogenous short-term speculation. For a given positive level of residual pay-off uncertainty, if liquidity trades display low persistence, rational investors act like market makers and accommodate the order flow and prices are farther away from fundamentals compared to consensus. This defines a “Keynesian” region; the complementary region is “Hayekian” in that rational investors chase the trend and prices are systematically closer to fundamentals than average expectations. The standard case of no residual uncertainty and liquidity trading following a random walk is on the frontier of the two regions and identifies the set of deep parameters for which rational investors abide by Keynes' dictum of concentrating on an asset “long-term prospects and those only”. The analysis also explains momentum and reversal in stock returns and how accommodation and trend-chasing strategies differ from these phenomena.